Carbon capture turned upside down: high-temperature adsorption & low-temperature desorption (HALD)1. Issue 8 (29th August 2015) - Joos, Lennart; Lejaeghere, Kurt; Huck, Johanna M.; Van Speybroeck, Veronique; Smit, Berend
<x xml:space="preserve">Abstract</x> Screening the international zeolite database identified the most promising materials for high-temperature adsorption & low-temperature desorption.